Identification of Near-Pan-neutralizing Antibodies against HIV-1 by Deconvolution of Plasma Humoral Responses - Sajadi, Mohammad Mohseni; Dashti, Amir; Rikhtegaran Tehrani, Zahra; Tolbert, William D.; Seaman, Michael S.; Ouyang, Xin; Gohain, Neelakshi; Pazgier, Marzena; Kim, Dongkyoon; Cavet, Guy; Yared, Jean; Redfield, Robert R.; et al. (Cell, 2018)
Anti-HIV-1 envelope broadly neutralizing monoclonal antibodies (bNAbs) isolated from memory B cells may not fully represent HIV-1-neutralizing profiles measured in plasma. Accordingly, we characterized near-pan-neutralizing antibodies extracted directly from the plasma of two “elite neutralizers.” Circulating anti-gp120 polyclonal antibodies were deconvoluted using proteomics to guide lineage analysis of bone marrow plasma cells. In both subjects, a single lineage of anti-CD4-binding site (CD4bs) antibodies explained the plasma-neutralizing activity. Importantly, members of these lineages potently neutralized 89%–100% of a multi-tier 117 pseudovirus panel, closely matching the specificity and breadth of the circulating antibodies. X-ray crystallographic analysis of one monoclonal, N49P7, suggested a unique ability to bypass the CD4bs Phe43 cavity, while reaching deep into highly conserved residues of Layer 3 of the gp120 inner domain, likely explaining its extreme potency and breadth. Further direct analyses of plasma anti-HIV-1 bNAbs should provide new insights for developing antibody-based antiviral agents and vaccines. [Display omitted] •HIV neutralizing activity is understood via plasma anti-gp120 response deconvolution•Near-pan-neutralizing activity is commonly traced to one anti-CD4bs IgG lineage•Plasma bNAbs persist and function as a minor fraction of the polyclonal response•Plasma anti-CD4bs mAbs have unique features and near-pan neutralizing properties An HIV-neutralizing antibody achieves near-pan-neutralizing activity through recognition of a highly conserved, difficult-to-access region of the viral gp120 glycoprotein.